The Level of Proficiency in Verbal and Non-Verbal Interpersonal Communication Among Undergraduate Technology Students at FPTV, UTHM - AHMAD, MUHAMMAD HAKIM; Ali, Azita (Research and Innovation in Technical and Vocational Education and Training, 2024)
Communication represents an indispensable skill for every student. The active engagement of students in both verbal and non-verbal communication significantly influences their academic performance. Nonetheless, certain students fail to attain mastery in verbal and non- verbal communication skills, impacting their employability immediately after graduation. Consequently, this study aims to identify the proficiency levels of verbal and non-verbal communication among Bachelor of Technology students at FPTV. The study adopts a survey design utilizing a quantitative approach, employing a questionnaire to collect data from 252 technology undergraduate students across three cohorts. The data undergoes analysis through descriptive statistical methods, including mean values and standard deviation, alongside the Mann-Whitney U test to discern gender-based differences. The study’s results indicate a high level of proficiency in verbal and non-verbal communication among technology undergraduate students. Furthermore, the findings reveal no significant difference in the mastery of verbal and non-verbal communication based on gender. Ultimately, the majority of Bachelor of Technology students at FPTV demonstrate adeptness in both verbal and non-verbal communication. This study’s impact extends to informing future research endeavors exploring the broader landscape of verbal and non-verbal communication mastery.